Control of non-minimum phase system using inverse response compensator with different approximations. (4th July 2022) - Yadav, Manish; Patel, Hirenkumar G.
This paper aims to control non-minimum phase systems with dead time in the presence of uncertainty and disturbances. The series cascade control scheme is utilised to motivate such problems, specifically for slow process dynamics and actuator nonlinearities. The internal model control (IMC) is utilised for the inner loop controller, while the outer loop controller is designed via fractional-filter-based IMC strategy with an inverse response and dead time compensator. The work's uniqueness lies in designing the outer loop controller via Taylor series, Pade and all pole approximation after embedding the fractional filter, dead time and inverse response compensator. The robustness test is carried out via sensitivity analysis. Two non-minimum phase dead time systems are utilised to demonstrate the usefulness of the proposed control strategy.